Occurrence of Cteisa hirta Solier, 1835 (Tenebrionidae, Alleculinae) in an abandoned nest of a social wasp (Vespidae: Polistinae) - de Castro Jacques, Gabriel; Carvalho Tavares, Maryá Cristina; Coelho Francisco, Sheliane Cristina (Acta Biológica Catarinense, 2024)
Abandoned nests of social wasps (Vespidae: Polistinae) are often occupied by other arthropods such as ants, spiders, termites, bees, and solitary wasps. However, there are no records of any species of Coleoptera occupying these structures. Therefore, this work aims to report the occurrence of a beetle in an abandoned nest of a social wasp. The presence of the beetle Cteisa hirta (Tenebrionidae, Alleculinae) was observed in a nest of the genus Polistes, at IFMG - Campus Bambuí on March 9, 2023. As only one nest was recorded with the presence of a beetle, it can be suggested that this occupation is casual, but further studies need to be carried out to confirm that the use of abandoned nests by Tenebrionidae, or another family of Coleoptera, is not frequent.